Excellence-Prior Eudaimonism - Herdt, Jennifer A. (Journal of religious ethics, 2019)
Eudaimonism is often regarded as egoistic. If it recommends that agents pursue their own good because it is their own good, it is guilty as charged. But excellence-prior eudaimonism offers a non-egoistic alternative to this welfare-prior eudaimonism. Excellence-prior eudaimonism recommends that an agent live in a way that is in fact good for the agent, but it does not regard the agent's own good as necessarily that for the sake of which the agent acts, nor does it regard living well as justified by the fact that it is good for the agent, but simply because it is good. The Christian eudaimonisms of Augustine and Aquinas are best understood as deepened forms of excellence-prior eudaimonism.